Analisis Financial Distress dengan Menggunakan Metode Altman (Z-Score) dan Springate (S-Score) pada PT. Fast Food Indonesia Tbk - Budi Utami; Mujiyani; Erna Kustyarini; Sri Sapto Darmawati (Jurnal Aplikasi Perpajakan, 2025)
The purpose of this research is to analyze the potential financial distress of PT. Fast Food Indonesia Tbk for the period 2022–2024. The analytical method applied in this research is descriptive quantitative analysis. The data used are secondary data in the form of annual financial statements for the period 2022–2024 obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id) and the official website of PT. Fast Food Indonesia Tbk (www.kfcku.com). The analytical tools used are four ratios of the Altman (Z-Score) and Springate (S-Score) models. The results show that the financial distress analysis using the Altman (Z-Score) model for PT. Fast Food Indonesia Tbk in the period 2022–2024 indicates Z < 1.1, which reflects a condition of “financial distress.” Meanwhile, the analysis using the Springate (S-Score) model shows S<0,862 which also reflects a condition of “financial distress”. Then, the accuracy level of this study shows that the Altman model has an accuracy rate of 100% and the Springate model also 100%.